Do SSRIs and SNRIs reduce the frequency and/or severity of hot flashes in menopausal women - Stubbs, Chris (J Okla State Med Assoc, 2017)
CLINICAL QUESTION: In menopausal women who experience regular hot flashes, does treatment with selective serotonin reuptake inhibitors (SSRIs) or serotonin-norepinephrine reuptake inhibitors (SNRIs) reduce the frequency and/or severity of hot flashes? ANSWER: Yes. Review of the literature suggests that treatment with SSRIs or SNRIs reduces the frequency and severity of hot flashes in menopausal and post-menopausal women. Studies demonstrated that paroxetine (Paxil), citalopram (Celexa) and escitolapram (Lexapro) were the most effective SSRIs, and venlafaxine (Effexor) was the most effective first line SNRI, with desvenlafaxine as a second option. The most common side effects reported for both SSRIs and SNRIs are nausea and constipation, with most resolving within the first week of treatment. SNRIs have been associated with increased blood pressure in some patients and should be used with caution in women with hypertension. Women with a history of breast cancer and taking tamoxifen should avoid SSRIs, which have been shown to interfere with tamoxifen metabolism. SNRIs are the safest drugs for this population. Treatment choice should be patient-specific and begin with the lowest dose available. LEVEL OF EVIDENCE FOR THE ANSWER: A SEARCH TERMS: SSRI, SNRI, hot flashes, vasomotor symptoms, menopause SEARCH CONDUCTED: August 2014, February 2016 and August 2016 INCLUSION CRITERIA: menopausal, perimenopausal or postmenopausal women 18 years of age or older with frequent and/or severe vasomotor symptoms, meta-analyses, systematic reviews, randomized controlled trials, cohort studies. EXCLUSION CRITERIA: pre-menopause, anxiety, depression, panic disorder, bipolar disorder, co-morbid conditions.